Expression patterns of melanin‐related genes are linked to crypsis and conspicuousness in a pumpkin toadlet - Monteiro, Juliane P. C. (2024)
Colour signals play pivotal roles in different communication systems, and the evolution of these characters has been associated with behavioural ecology, integumentary production processes and perceptual mechanisms of the species involved. Here, we present the first insight into the molecular and histological basis of skin colour polymorphism within a miniaturized species of pumpkin toadlet, potentially representing the lowest size threshold for colour polytypism in tetrapods. Brachycephalus actaeus exhibits a coloration ranging from cryptic green to conspicuous orange skin, and our findings suggest that colour morphs differ in their capability to be detected by potential predators. We also found that the distribution and abundance of chromatophores are variable in the different colour morphs. The expression pattern of coloration related genes was predominantly associated withmelanin synthesis (including dct, edn1, mlana, oca2, pmel, slc24a5, tyrp1 and wnt9a). Up-regulation of melanin genes in grey, green and brown skin was associated with higher melanophore abundance than in orange skin, where xanthophores predominate. Our findings provide a significant foundation for comparing and understanding the diverse pathways that contribute to the evolution of pigment production in the skin of amphibians.